Copper-catalyzed synthesis of aminoquinolines from β-(2-aminophenyl)-α, β-ynones using DMF as dual synthon. Issue 48 (27th May 2020) - Ganesan, Balaji; Govindan, Karthick; Senadi, Gopal Chandru; Kandasamy, Mohanraj; Lin, Wei-Yu
Abstract : The utilization of DMF as a dual synthon to serve as a methine source to introduce C2 carbon and nitrogen source to incorporate amino functionality in the 4 th position of quinoline under Cu-catalysis. Abstract : A new and efficient method has been developed for the synthesis of 4-aminoquinoline through aerobic Cu(i )-catalyzed cyclization of β-(2-aminophenyl)-α, β-ynones. Under the optimized conditions, DMF could serve as a methine source to introduce C2 carbon and a nitrogen source to incorporate amino functionality in the 4 th position. Mechanistic studies using 13 C- and DMF- d 7 revealed that the methine group was derived from a methyl substituent.